Antioxidant capacity and immunomodulatory effects of a chrysolaminarin-enriched extract in Senegalese sole. Issue 82 (November 2018) - Carballo, Carlos; Chronopoulou, Evangelia G.; Letsiou, Sofia; Maya, Claudia; Labrou, Nikolaos E.; Infante, Carlos; Power, Deborah M.; Manchado, Manuel
Abstract: The microalgae are an important source of bioactive molecules including β-glucans that can be used as immunostimulants in aquaculture. In the present study, the antioxidant capacity, cytotoxicity and immunomodulatory activity of a chrysolaminarin-enriched extract obtained from the diatom Phaeodactylum tricornutum was evaluated. The extract showed a higher total antioxidant activity as determined by ORAC and FRAP assays and a lower DPPH scavenging activity than particulate yeast-β-glucan. The cytotoxicity test indicated that extract concentrations higher than 0.01% w/v could impair cell viability of human dermal fibroblasts. To evaluate the immunomodulatory activity, juvenile soles were intraperitoneally injected with the chrysolaminarin-enriched extract suspended in coconut oil (1 mg/fish) followed by a reinjection at 7 days. A sham group injected with the carrier solution was maintained as a negative control. Cumulated mortality of fish injected with the chrysolaminarin-enriched extract was 29.4% after six days and no mortality was recorded after extract reinjection. Expression analyses of fifteen genes related to the innate immune system in kidney, spleen and intestine showed temporal and organ-specific responses. A rapid (2 days post-injection; dpi) and strong induction of the pro-inflammatory il1b and the antimicrobial peptide hamp1 in the three immunological organs, the hsp90aa in kidney and spleen, irf3 in intestine and c3 in spleen was observed indicating a potent inflammatory response. The recovery of steady-state levels for all activated genes at 5 dpi, and the down-regulation of c-lectin receptor as well as some interferon-related genes ( ifn1, irf1, irf3, irf8, irf9 and mx ) in kidney and cxc10 in spleen indicated that the soles were able to activate a homeostatic response against the β-glucan insult. The reinjection of the chrysolaminarin-enriched extract did not activate a new inflammatory response but reduced the mRNA levels of hsp90aa and irf3 indicating that soles developed some resistance to β-glucans. Overall, these results reveal this enriched extract as a novel and potent source of β-glucans with antioxidant and immunomodulatory capacity suitable for immunostimulation in aquaculture. Highlights: The chrysolaminarin-enriched extract exhibits a higher antioxidant capacity than particulate yeast-β-glucan. Intraperitoneal injection of chrysolaminarin-enriched extract provokes a moderate mortality and activates a fast and potent inflammatory response with organ-specific expression patterns. Steady-state levels of pro-inflammatory genes are restored at 5 days post-injection and no inflammatory response or mortality occurs if microalgal extract is reinjected after 7 days.